Sequential or simultaneous-integrated boost in early-stage breast cancer patients: trade-offs between skin toxicity and risk of compromised coverage - Changyou Zhong; Minfeng Huang; Haidong Yu; Jun Yuan; Ruilian Xie; Zhenzhen Lai; Shanzhou Niu; Chunbo Tang (Radiation Oncology)
Abstract Purpose To determine the dosimetric effects of set-up errors on boost coverage, and compares skin toxicity of sequential and simultaneous boost techniques for left-sided breast cancer. Materials and methods This retrospective study included 23 early-stage breast cancer cases. Single isocenter HFWBI-SIB(s-SIB), single isocenter HFWBI-SB(s-SB) and dual isocenter HFWBI-SB(d-SB) were planing. Rotations of 0.5°, 1°, and 2° coupled with translationals of 0.5 mm, 1.0 mm, and 2.0 mm were applied along three orthogonal axes. The dose to 95% of the PTV (D95) and the volume covered by 95% of the prescribed dose (V95) were evaluated using GEE univariate analysis to determine how PTV coverage was related to 1/CIRTOG, PTVboost volume, PTVboost separation to isocenter. The relationship between the high-dose regions within the PTVbreast and Ratio_V was evaluated using univariate analysis. Results The s-SIB had optimal target coverage and lower high-dose volume, but it increased the risk of compromised coverage to tumor bed. For the s-SB technique, V95 exceeded 95% under all setup errors. At 2.0° coupled with 2.0 mm, s-SIB and d-SB exhibited V95 values below 95% in 34.8% and 8.7% of cases, respectively. At other setup errors, both s-SIB and d-SB demonstrated V95 values greater than 95%. Notably, high-dose regions such as V105%, V107%, and V110% within the PTVbreast across the three techniques displayed a significant correlation with Ratio_V. Conclusion Simultaneous-integrated boost for early-stage breast cancer can reduce skin toxicity compared to sequential techniques but with the risk of compromising tumor bed coverage.